The leaching of mineral nitrogen forms from light soil fertilized with compost and sewage sludge - Rajmund, Agnieszka; Czyżyk, Franciszek; Paszkiewicz-Jasińska, Anna; Kopacz, Marek (Geology, Geophysics and Environment, 2018)
The research was carried out in the years 2003-2013 in lysimeters filled with loamy sand. The leachate was tested in three variants: Z - no fertilization, S - 20 g-m-2 of N delivered annually in sewage sludge and C - 20 g-m-2 of N in the form of compost. The lysimeters were planted with Miscanthus giganteus, which is an energy plant with a high demand for water and nutrients. The amount of leaching of mineral nitrogen forms was determined on the basis of measured volumes of leachates from the soil and volumes of ammonium nitrogen (N-NH4) and nitrate nitrogen (N-NO3) contained in them. The research results showed a significant increase in the average content of mineral nitrogen forms in the effluents from the fertilized soil (S - 6.8 mg-dm-3 of N-NO3 and 0.3 mg-dm-3 of N-NH4, C - 7.8 mg-dm-3 of N-NO3 and 0.4 mg-dm-3 of N-NH4), compared to their concentrations in the leachates from non-fertilized soil (Z - 2.1 mg-dm-3 of N-NO3 and 0.2 mg-dm-3 of N-NH4). The content of mineral forms of nitrogen, in particular N-NO3, were similar in both fertilization variants. The lowest concentrations of mineral nitrogen in the leachates occurred in the third and fourth year after planting Miscanthus giganteus, when it entered the period of the highest yield. In the fifth year, due to a cold, snowless winter, there was a weakened growth of plants, which resulted in an increase in the concentration of mineral nitrogen in the leachates from the fertilized soil. It follows that in addition to the intensity of precipitation, the collection of this component by plants primarily influences nitrogen leaching from the soil. The general amount of mineral nitrogen leached from the soil was not large and amounted Z - 2.5 kg-m-2, S - 6.7 kg-m-2, C - 6.4 kg-m-2. This testifies to the intense collection of this form of nitrogen by Miscanthus giganteus.